Factores jurídico procesales inquisitivos en el codigo procesal penal que impiden consolidar el modelo acusatorio en el Perú - Burgos Mariños, Víctor Alberto Martín (2011)
The present investigation aimed to determine the existence of procedural legal factors questioning in the text of the Code of Criminal Procedure to prevent the consolidation of the adversarial model in Peru. To perform this research analyzes the new Code of Criminal Procedure, Case casatorias, full jurisdictional monitoring reports of the courts which applied the new Criminal Procedure Code, the international human rights instruments, foreign law in Chile and Colombia and reports to monitor the reform process in Latin America, found that: a) The criminal procedure reform in Peru, has not been accompanied by reforms to the Constitution and the organic laws to conform to the adversarial model; b) Exist in the Criminal Procedure Code inquisitive lags rules that maintain existing culture and practices of the mixed model of inquiry, as the prevalence of literacy and the record, the use of detention as early penalty, the person as an object of test, the interrogation of the accused as the first action of the trial evidence, rigid order, the performance of the office of Judge affecting adversarial trial and the right to a second hearing; c) The literal interpretation of the rules of the Code also may affect the consolidation of the adversarial model, in particular, the design of an efficient investigation based on coordinated work between the National Police and the Public Ministry, orality in pretrial hearings oral alternative solutions in the intermediate stage and the right to challenge; and, d) Article X of the Preliminary Title Code of Criminal Procedure provides that the interpretation of the rules of the Code, must be in accordance with the guiding principles of the Preliminary, ie should not be a literal interpretation, but rather a constitutional interpretation.